Myocardial Infarction in Young Women - o’g’li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2024)
The low alertness of physicians and women due to the rare incidence of myocardial infarction in young women, often atypical clinical presentation, and frequent lack of obstructive coronary artery disease accounts for the issue of timely diagnosis. According to Russian researchers, the incidence of acute myocardial infarction in women aged 35–44 years in Russia in 2014 was 0.2%. Foreign studies have shown that slightly over half of young women with ST-elevation myocardial infarction experience typical chest pain. Our case reports highlight the challenges in diagnosing myocardial infarction in young women, and the impact of both gender-related and non-gender-related risk factors. Although there is no obstructive coronary atherosclerosis, myocardial infarction in young women can have a severe course and lead to complications such as cardiac aneurysms and chronic heart failure.